A woman's work is never done? Fund-raising perception and effort among female state legislative candidates - Jenkins, Shannon (2007)
The lack of female politicians has been attributed to a lack of female candidates for office. However, the reason why there are so few female candidates is not clear. the author examines whether differences in fund-raising perceptions and effort between female and male state legislative candidates contribute to the lack of female candidates. The results indicate that women do tend to be more concerned about fund-raising, as is evidenced by greater effort devoted to this campaign function as compared to their male counterparts. Women use more techniques and rely on more sources to secure funds for their campaigns. This suggests that part of the reason women are reluctant to run for office may be due to the fact that they will have to devote more effort to a task candidates generally find distasteful. - Reproduced.
Keywords: Women in politics